2019
DOI: 10.1039/c9na00075e
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient catalytic/sonocatalytic reduction of 4-nitrophenol and antibacterial activity through a bifunctional Ag/ZnO nanohybrid material prepared via a sodium alginate method

Abstract: In this work, a bifunctional nanohybrid silver/zinc oxide material (Ag/ZnO) has been synthesized by a rapid route using sodium alginate simultaneously as a sacrificial template and silver reducing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…These spectral changes correspond to the formation of the reaction product ( p‐ NA) and the consumption of the reactive (DNB), respectively. Furthermore, a clear isosbestic point is observed at λ=300 nm indicating the absence of intermediates and/or product decomposition [26–28] . The complete conversion of DNB to p‐ NA catalyzed by 2 and 3 occurs around 30 min while when it is catalyzed by 1 the conversion occurs around 90 min; these results are favorable since other types of MNP as catalysts may take longer.…”
Section: Resultsmentioning
confidence: 94%
“…These spectral changes correspond to the formation of the reaction product ( p‐ NA) and the consumption of the reactive (DNB), respectively. Furthermore, a clear isosbestic point is observed at λ=300 nm indicating the absence of intermediates and/or product decomposition [26–28] . The complete conversion of DNB to p‐ NA catalyzed by 2 and 3 occurs around 30 min while when it is catalyzed by 1 the conversion occurs around 90 min; these results are favorable since other types of MNP as catalysts may take longer.…”
Section: Resultsmentioning
confidence: 94%
“…It was reported that bacterial growth could be inhibited by specific disruption mechanisms present between composites and the surface of the bacteria (generation of H 2 O 2 , reorientation and rearrangement of the surface of the bacteria) . Moreover, the bacterial activity of composites also depends on particle size, particle surface chemistry, stability, and concentration in the growth medium, which is inversely proportional to the size and concentration of the particles …”
Section: Resultsmentioning
confidence: 99%
“…Electrical, optical, chemical and magnetic properties of these materials strongly exist in many application domains, including medicine, packaging, optical machine and electronic devices . Among these composites, there are noble metal/metal oxides such as Ag/ZnO, Ag/TiO 2 , Au/ZnO, Au/CuO, and metal oxides/metal oxides such as ZnO/TiO 2 , ZnO/CuO, NiO/CuO, La 2 O 3 /ZnO . composites are usually synthesized using many routine methods comprising sol‐gel, solvothermal, precipitation, gelation using biopolymers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ag/ZnO nanoparticles were also reported for photoreduction and antibacterial activities. 24 Whereas, Jeyachitra et al 25 have reported the synthesis of Ni and Ag codoped ZnO NPs for dye degradation applications. Azfar et al 26 have also reported the synthesis of Ni and Ag codoped ZnO NPs by using the sol–gel method.…”
Section: Introductionmentioning
confidence: 99%